ANXIETAS AND COPING MECHANISM OF THE FINAL SEMESTER NURSING STUDENTS IN THE SITUATION OF COVID-19 - Ekayamti, Endri (Universitas Airlangga, 2020)
Introduction: The Covid-19 pandemic which hit 215 countries has an impact on all aspects of life for the world community, including Indonesia. One of the most significant impacts is the world of education. The government policy towards education is to do distance learning or learning from home. This changing learning system raises various problems, especially for nursing students. Competencies that must be mastered by nursing students, especially at the final level, apart from a cognitive perspective, are also abilities in the psychomotor field and skills where this ability is obtained by laboratory practice and the ability to provide direct nursing care to patients in the hospital. This change raises its own problems for student psychology, students have feelings of anxiety and worry about their studies. Students also questioned whether they can graduate at the specified time. This study aims to analyze the relationship between anxiety and coping mechanisms in final semester nursing students during the COVID-19 pandemic. Methods: This study used a descriptive correlational design with a cross sectional approach. The population is students of the Akper Pemkab Ngawi in the final semester of the 2018/2019 academic year, the sampling technique used is total sampling with a total of 110 respondents. The anxiety instrument used is the STAI measurement scale and the scale of the coping mechanism. The statistical test used is the Pearson correlation. Results: The results obtained were that there was a significant relationship between anxiety and the coping mechanism used by students with a value of p = 0.007 for the state anxiety scale and p = 0.000 for the trait anxiety scale. Conclusion: Based on the results of the study, it can be concluded that the final semester student anxiety during the Covid-19 pandemic is more towards momentary anxiety, where this could have happened because the feeling of uncertainty in their study was related to the covid-19 pandemic